Notes on Cattle Breeding in Milan in the Second Half of the Thirteenth Century (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
In Milan, in the thirteenth century, livestock was a very important resource, that is little known today, because of the few sources available. The contracts of soccida written by the notary Giovannibello Bentevoglio in 1271 show that the breeding of sheep and cattle involved a lot of little entrepreneurs in the city and in the countryside. The great demand for meat and leather from the city market made this activity very profitable.
Keywords: Livestock; Cattle; Milan; 13th century